1960
DOI: 10.1139/m60-033
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Carbohydrates and Amino Acids by Micrococcus Radiodurans

Abstract: The nutrition and metabolism of a recently isolated Micrococcus species resistant to closes of gamma radiation as high as 6 × 106 r.e.p. were studied by manometric and radioactive tracer techniques. Methionine, the only amino acid shown to be essential in a chemically defined medium, appears to be rapidly incorporated into the cells. DL-Glutamic acid is readily metabolized, the D isomer apparently after an initial lag. Among the simple carbohydrates, fructose, glucose, and glycerol are readily utilized. The op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…This ruled out the possibility of incomplete oxidation of glucose had occurred. Thus, glucose could only be released mainly as CO 2 by enzymes of the tricarboxylic acid cycle, which was fully functional in this organism (25). The potential energy released from glucose oxidation is very large (G f°ϭ Ϫ917.22).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This ruled out the possibility of incomplete oxidation of glucose had occurred. Thus, glucose could only be released mainly as CO 2 by enzymes of the tricarboxylic acid cycle, which was fully functional in this organism (25). The potential energy released from glucose oxidation is very large (G f°ϭ Ϫ917.22).…”
Section: Discussionmentioning
confidence: 94%
“…This led us to examine the glucose metabolism of this organism in detail. Raj et al (25) showed that D. radiodurans has a functional PPP. We confirmed their results and further showed that the enzymatic activity of G6PDH in D. radiodurans was more than fourfold higher than the G6PDH activity in E. coli (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…By a process of elimination, we identified minimal nutrient constituents and the concentrations of these nutrients necessary for luxuriant growth ( Table 1). The synthetic medium which we developed for D. radiodurans is distinct from the media described by other workers (25,28) in that it is much simpler and growth of D. radiodurans in the medium is completely dependent on a nonamino carbon source (e.g., fructose) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…radiodurans was first isolated from gamma-irradiated canned meat in Oregon by Anderson et al (14) and was named Micrococcus radiodurans on the basis of its morphological and physiological characteristics (502). A morphologically similar M. radiodurans strain, strain Sark, was later isolated as an air contaminant in a hospital in Ontario, Canada (R. G. E. Murray and C. F. Robinow, presented at the Seventh International Congress of Microbiology, 1958).…”
Section: Ecology Of D Radioduransmentioning
confidence: 99%
“…RADIODURANS OXIDATIVE STRESS RESISTANCE 137 phosphate pathway (PPP), the tricarboxylic acid cycle, and glyoxylate bypass (381) ( Table 2). The PPP is highly active in D. radiodurans (502), with the activity of glucose-6-phosphate dehydrogenase (G6PDH) (the marker enzyme for PPP) being 4-fold higher than that in Escherichia coli (683). G6PDH is upregulated in gamma-irradiated cells (677), and mutants defective in G6PDH are sensitive to UV light, hydrogen peroxide (H 2 O 2 ), and MMC (367,682).…”
Section: Vol 75 2011mentioning
confidence: 99%